Identification of microRNA targets for Isoforms of pro-apoptotic factor BIM. - Hong, Hui Qi. (2013)
BCL-2-interacting mediator of cell death (BIM) is a prominent regulator of the intrinsic apoptotic pathway. Aberrant BIM expression has been implicated in a multitude of diseases. Intriguingly, post-transcriptional regulation, modulated primarily by cis-elements in the 3’untranslated regions (UTRs), accounts for approximately 60-80% of overall regulatory effects on expression of protein-coding genes. Identification of such cis-elements as microRNA (miRNA) targets in BIM 3’UTRs is therefore of intense interest, as these cis-elements are potential therapeutic targets for